The effect of liquidity and company size on company value with profitability as a moderation variable - Kartika, Yulia Elsa; Wiagustini, Ni Luh Putu (International Journal Labs, 2024)
The purpose of this study was to determine the effect of liquidity and company size on firm value with profitability as a moderation variable. This study used 29 samples with 5 years of observation with the results of 145 observation samples in F&B companies listed on the Indonesia Stock Exchange for the period 2018-2022. The analysis technique used in this study is Moderated Regression Analysis (MRA), using Eviews 11 software. The results show that liquidity has a positive effect on the value of the company, this finding shows that companies with high profitability can have higher company values, even with low liquidity. These findings are important for investors and creditors in making investment and credit decisions. For company management, it is recommended to optimize inventory such as ensuring that inventory levels remain ideal for smooth operations and low storage costs. Strict credit policies and incentives for faster payments should be implemented to accelerate the recovery of trade receivables.